(untitled) (Research, Society and Development, 2024)
The aim of this review was to evaluate the efficacy of tai chi as a therapeutic intervention for Parkinson’s disease (PD). The search was carried out using Google Scholar databases, CAPES Journal databases, and PubMed, covering the period from 2013 to 2023, without language restrictions, including all types of clinical studies, regardless of methodological design. Of the seven studies selected, one randomized controlled trial indicated that tai chi performed better on the Unified Parkinson’s Disease Rating Scale (UPDRS) and in the prevention of falls, when compared to conventional exercise. Another randomized controlled trial did not identify significant benefits of tai chi on locomotor capacity over other physical activities. A third randomized clinical trial revealed no impact of tai chi on UPDRS scores and PD-specific questionnaires, when compared to a control group on a waiting list. The remaining studies consisted of one non-randomized clinical trial and three uncontrolled studies. Overall, the data suggest that randomized controlled trials evaluating tai chi as an approach to PD are feasible, but still limited. Many of these studies have methodological weaknesses, such as inadequate design, incomplete reporting of results, small sample sizes, and the absence of adequate peer review. In summary, the available evidence is insufficient to recommend tai chi as an effective intervention for PD. Further research is imperative to explore potential benefits of tai chi for individuals with PD.